Study on the effect of salt concentration on growth and Astaxanthin accumulation of microalgae Haematococcus pluvialis as the initial basis for two phase culture of astaxanthin production - Tam, Luu Thi; Hoang, Dinh Duc; Ngoc Mai, Dinh Thi; Hoai Thu, Ngo Thi; Lan Anh, Hoang Thi; Hong, Dang Diem (Academia Journal of Biology, 2012)
Microalga Haematococcus pluvialis Flotow is one of the natural sources of astaxanthin, a pigment widely used in aquaculture, food, pharmaceutical and nutraceutical industries. In the present study, we investigated the effect of high NaCl concentrations on growth and astaxanthin accumulation in the microalga. Growth was observed under different salt concentrations (0.8%, 1.5% and 2.5% NaCl) according to two - phase culture mode. The obtained results have indicated that the high NaCl concentrations caused an increase in carotenoid content per cell and a decrease in the algal growth. The best carotenogenic condition by addition of salt was obtained at 2.5% NaCl under high temperature. Astaxanthin content per cell increased 4.8 folds in comparison to the initial value, from 10 pg.cell-1 to 48 pg.cell-1 after 15 days of salt stress. We observed that the accumulation of total lipid content was correlated with an increasing in astaxanthin content. The total lipid content of control was 15 ± 0,35% of dry cell weight whereas that of cell exposed to salt stress was 19% ± 1,3% and 26 ± 0.12% at 1.5% and 2.5% NaCl concentrations, respectively. This study will be an initial basis for the two phase culture process to obtain astaxanthin rich Haematococcus pluvialis biomass